(untitled) (Journal of the Management Sciences, 2023)
This study examined gender consideration and entrepreneurship development in Anambra State, Nigeria. Specifically, it investigated the effect of age of women, education of women and economic status of women on setting up a business in Anambra State, Nigeria on a sample of 278 respondents. Data collected was analyzed using descriptive statistics (frequencies, percentages, mean, and standard deviation) and the inferential statistics such as t-test statistics and the linear regression model. The analysis of the study revealed the following findings: Age of women has significant influence on setting up a business in Anambra State, Nigeria. Education of women has significant influence on setting up a business in Anambra State, Nigeria. Economic status of women has significant influence on setting up a business in Anambra State, Nigeria. Based on the findings, the study recommends that women should be encouraged to be properly mentored by well experienced women entrepreneur. This will enable them develop business maturity because age has been found to significantly influence setting up a business in Anambra State, Nigeria; the government should continue to provide skill acquisition programmes for women because education of women is found to significantly influence setting up a business in Anambra State, Nigeria and the government should establish a supervised credit scheme to ensure adequate funding for setting up a business.